The Effects of Cardiovascular Risk Factors on Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) Performance in Cognitively Healthy Older Adults. (24th October 2019) - De Vito, Alyssa N; Bernstein, John P K; Weitzner, Daniel; Calamia, Matthew; Keller, Jeffrey N
Abstract: Objective: The current study investigated the differential impact cardiovascular risk factors (CVRFs) on Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) performance in a large, cognitively healthy, older adult sample across 4 years. Method: Participants were 486 individuals recruited through a longitudinal aging research study in the southeastern United States. Participants were 69.3% female, an average of 69.96 years old (SD = 6.58), 16.32 years of education (SD = 2.27), and Mini-Mental Status Exam score of 29.12 (SD = 1.16). Participants completed the RBANS at baseline and yearly thereafter, as well as the Uniform Data Set demographic and health questionnaires and the Geriatric Depression Scale. Results: Multilevel modeling was conducted using standardized RBANS index scores. Overall, across indices, performance generally improved across time consistent with practice effects from repeated testing. Some CVRFs were associated with worse performance over time. For example, individuals with hypertension performed more poorly on immediate memory over time ( t  = −2.06, p  < .05). Other CVRFs (e.g., BMI) were not associated with baseline performance or performance over time. ( p  > .05). Conclusions: CVRFs differentially affect RBANS performance over time. These results extend previous cross-sectional findings regarding the impact of different cardiovascular health risks to a large, cognitively healthy, longitudinal sample.